2014
DOI: 10.1002/cam4.327
|View full text |Cite
|
Sign up to set email alerts
|

Fruits, vegetables, and bladder cancer risk: a systematic review and meta‐analysis

Abstract: Smoking is estimated to cause about half of all bladder cancer cases. Case–control studies have provided evidence of an inverse association between fruit and vegetable intake and bladder cancer risk. As part of the World Cancer Research/American Institute for Cancer Research Continuous Update Project, we conducted a systematic review and meta-analysis of prospective studies to assess the dose–response relationship between fruit and vegetables and incidence and mortality of bladder cancer. We searched PubMed up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 34 publications
(102 reference statements)
1
41
0
6
Order By: Relevance
“…If we had been as inclusive as Krueger et al ., our estimate for the economic burden of inadequate consumption of vegetables and fruit would have been $CAN 3·8 billion per year. The estimate of the economic burden of inadequate vegetables and fruit consumption should be considered an economic burden in addition to the estimates for smoking tobacco, excess body weight and physical activity by Krueger et al ., because the relative risks used in our estimation originated from meta-analyses of mostly clinical trials and observational studies that were adjusted for tobacco use, excess body weight, and physical activity among other confounders ( 4 , 20 – 24 , 28 ) . By expanding the estimates by Krueger et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If we had been as inclusive as Krueger et al ., our estimate for the economic burden of inadequate consumption of vegetables and fruit would have been $CAN 3·8 billion per year. The estimate of the economic burden of inadequate vegetables and fruit consumption should be considered an economic burden in addition to the estimates for smoking tobacco, excess body weight and physical activity by Krueger et al ., because the relative risks used in our estimation originated from meta-analyses of mostly clinical trials and observational studies that were adjusted for tobacco use, excess body weight, and physical activity among other confounders ( 4 , 20 – 24 , 28 ) . By expanding the estimates by Krueger et al .…”
Section: Discussionmentioning
confidence: 99%
“…Based on these sources, we considered risk estimates for type 2 diabetes ( 21 ) , CVD (IHD, ischaemic stroke) ( 4 ) and cancers (lung ( 22 ) , colorectal ( 25 ) , oesophagus ( 20 ) , stomach/gastric ( 4 ) , bladder ( 24 ) , oral ( 20 ) , larynx ( 20 ) and breast ( 23 ) ). Because we were interested in the effect of the combination of vegetables and fruit, in cases where a meta-analysis reported separate effects of vegetables only and of fruit only, we considered the lower risk estimate.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, some epidemiologic studies examining cruciferous vegetables intake and bladder cancer risk, have shown no association of decreased risk . For example, a prospective study from Alpha‐Tocopherol Beta‐Carotene Cancer Prevention Study did not find an association between total fruits and vegetables intake or cruciferous vegetables intake and bladder cancer risk in smokers .…”
Section: Epidemiology Of Cruciferous Vegetables Isothiocyanates Andmentioning
confidence: 98%
“…Keeping in mind a report that 71% of the articles selected for meta-analysis do not lend themselves to DRMA [3], findings from nutritional epidemiological studies should be presented in a manner that would facilitate future meta-analyses. Under the current circumstances, DRMA should be considered as a method to be applied concurrently with the HLM or ICM, instead of replacing them [27][28][29].…”
Section: Discussionmentioning
confidence: 99%